Abul A’la Maududi and The Jamaat-I-Islami - Haikal, Husain (Al-Jami'ah Research Centre, 1980)
In His best known book, towards Undestanding Islam. Which has been translated into many different languages, Maududi states that unlike any other great religions Islam is not named either for its ”founder” or after the community and nation in which it was born. Islam as a matter of fact is an attributive title. Islam is an Arabic word and connotes submission, surrender, and obedience. As a religion, Ilam stands for complete submission and obedience to Allah. Such a life of obedience brings peace of the heart and establishes real peace in the society at large.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//